Demonstrating the Use of a Fungal Synthesized Quinone in a Redox Flow Battery. Issue 1 (3rd November 2022) - Wilhelmsen, Charlotte Overgaard; Kristensen, Sebastian Birkedal; Nolte, Oliver; Volodin, Ivan A.; Christiansen, Johan Vormsborg; Isbrandt, Thomas; Sørensen, Trine; Petersen, Celine; Sondergaard, Teis Esben; Lehmann Nielsen, Kåre; Larsen, Thomas Ostenfeld; Frisvad, Jens Christian; et al.
Abstract: Aqueous organic redox flow batteries (AORFBs) have gained increased interest as a promising solution to store energy from sustainable energy sources. Inspired by naturally occurring bio‐quinones, we here propose a new electrolyte based on the fungal compound phoenicin. Phoenicin was produced using the filamentous fungus Penicillium atrosanguineum at a concentration of 1.24 g L −1 liquid medium and extracted using ethyl acetate to a purity exceeding 95 %. The fungus may provide a benefit of high scalability of the biosynthesis‐based production of the electroactive substance. Here, we demonstrate the performance of biologically produced phoenicin as a negative electrolyte in an RFB against ferro/ferricyanide, as a proof of concept, giving an initial capacity of 11.75 Ah L −1 and a capacity decay of 2.85 % day −1 . For a deeper investigation of the battery setup, in situ attenuated total reflection infrared (ATR‐IR) spectra of the phoenicin electrolyte were recorded. Symmetric cell cycling was performed to study the stability of this bio‐based active material. Abstract : Biobased : The filamentous fungus can be used as an environmentally and sustainable benign source to produce the bio‐based quinone phoenicin. This natural compound shows electrochemical properties, which can be used as the active material in the negative electrolyte in a redox flow battery with results showing that biologically produced quinones may become a real competitor to the currently available synthetic quinones.